Women doing life : gender, punishment, and the struggle for identity - Lempert, Lora Bex (New York University Press, 2016)
How do women -- mothers, daughters, aunts, nieces and grandmothers -- make sense of judgment to a lifetime behind bars? In Women Doing Life, Lora Bex Lempert examines the carceral experiences of women serving life sentences, presenting a typology of the ways that life-sentenced women grow and self-actualize, resist prison definitions, reflect on and "own" their criminal acts, and ultimately create meaningful lives behind prison walls. Looking beyond the explosive headlines that often characterize these women as monsters, Lempert offers rare insight into this vulnerable, little studied population. Her gendered analysis considers the ways that women "do crime" differently than men and how they have qualitatively different experiences of imprisonment than their male counterparts. Through in-depth interviews with 72 women serving life sentences in Michigan, Lempert brings these women back into the public arena, drawing analytical attention to their complicated, contradictory, and yet compelling lives. Women Doing Life focuses particular attention on how women cope with their no-exit sentences and explores how their lifetime imprisonment catalyzes personal reflection, accountability for choices, reconstruction of their stigmatized identities, and rebuilding of social bonds. Most of the women in her study reported childhoods in environments where violence and disorder were common; many were victims before they were offenders. Lempert vividly illustrates how, behind the prison gates, life-serving women can develop lives that are meaningful, capable and, oftentimes, even ordinary. Women Doing Life shows both the scope and the limit of human possibility available to women incarcerated for life. -- Provided by publisher